Review: Teacher Researcher Perspectives on Parent Involvement - Catherine Compton-Lilly (Networks: An Online Journal for Teacher Research, 1999)
What is happening at your school to foster parent involvement? Where I teach, parent involvement is a constant struggle. Programs that promise to bring parents into the school come and go quickly; they are never well-attended and the parents who do attend the first session often do not return for the second. Teachers, observing this lack of involvement, complain that parents don't care and do not support the school. The rhetoric around our school blames parents when things go wrong for children at school.